Positive multifocal PSMA PET/CT in a patient with prostate cancer and follicular lymphoma - Dendl, Katharina; Merkel, Andreas; Kratochwil, Clemens; Choyke, Peter L.; Kleist, Christian; Cardinale, Jens; Haberkorn, Uwe; Giesel, Frederik L. (Clinical nuclear medicine, 2022)
Prostate-specific membrane antigen (PSMA) PET/CT is a highly reliable nuclear tracer for diagnostic imaging of prostate cancer. However, PSMA is also expressed by some nonprostatic tissues such as benign tumors, inflammatory processes, and malignant neoplasms. This case presents a patient with prostate cancer and follicular lymphoma undergoing PSMA PET/CT. Remarkably, both tumor entities were clearly detected in the scan. Yet, the 2 malignancies demonstrated rather different ranges in terms of SUVmax uptake values and therefore still enabled precise and accurate discrimination of prostate cancer and follicular lymphoma.
Gesehen am 19.01.2022